Penerapan Kompensasi Terhadap Korban Kejahatan Tindak Pidana Terorisme Studi Kasus Bom Bali - Kelik Caesar Saputra; Aldi Cahya Satria; M. Hamzah Al Ghafiki; Pramudita Mandala Sakti; Noufal Raihan Ghulam; Ripa Mahal Kabul Izati; Haykal Fahd Wijaya Muhammad; Rofiq Maulana Sandi (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The bombing incident that occurred in Bali in 2002 was a tragedy that attracted world attention, with victims reaching 202 deaths and more than 200 people injured. This tragedy occurred after the hijacked plane crashed into the World Trade Center towers in America in 2001, which increasingly increased global attention to the issue of terrorism. The aim of this research is to examine compensation for victims of terrorist crimes. This research method uses a descriptive qualitative research method with a normative juridical approach using secondary data in the form of documents and books regarding the object of this research, then this research uses 3 types of legal materials in the form of primary legal materials, secondary legal materials and tertiary legal materials. The findings of this research show that in Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims, victims of criminal acts of terrorism also receive protection for their personal security, family and property, and are free from threats. relating to testimony that will be, is being, or has been given and participating in the process of selecting and determining forms of security protection and support as well as providing information without pressure. Protection for victims of criminal acts of terrorism implemented in Indonesia is based on the 1945 Constitution of the Republic of Indonesia and Law Number 15 of 2003 concerning the Eradication of Criminal Acts of Terrorism. Bali bombing victims have the right to receive legal protection and compensation from the state for the acts of terrorism that occurred. They also receive protection for their personal security, family and property, and are free from threats related to the testimony they will, are giving, or have given.